Giant primary retroperitoneal seminoma: A case report - Janjušević, Nataša; Mirković, Darko; Jovanović, Milan; Vulović, Maja; Milev, Boško; Mitrović, Miroslav; Trifunović, Bratislav (Vojnosanitetski pregled, 2017)
Introduction. Primary extragonadal seminomas are rare tumors. There have been only a few cases of the primary retroperitoneal seminomas reported in the literature up to date. Case report. We reported a 56-year-old man with giant primary retroperitoneal seminoma presented with the enlargement of the left side of the abdomen and deep venous thrombosis of the left leg. Computed tomography of the abdomen showed a large tumor occupying the left part of the retroperitoneal space with 23 ´ 13 cm in diameter. Firm tumor mass having 25 ´ 15 cm in diameter was surgically removed from the left retroperitoneum. The tumor adhered the tunica adventitia of the aorta and it was carefully resected from the aortic wall. The diagnosis of seminoma was made during histopathological examination. The patient underwent chemotherapy. Two years after finished chemotherapy the patient accepted left orchiectomy with the aim of eliminating the possibility of the occult malignancy of the testicle. Histopathological analysis of the testicular tissue was normal and the diagnosis of primary retroperitoneal seminoma was confirmed. Conclusion. Despite its small incidence in general population, the diagnosis of retroperitoneal seminoma should be considered in male patients with nonspecific symptoms and with retroperitoneal tumor mass.